Human sulfatase‐1 inhibits the migration and proliferation of SMMC‐7721 hepatocellular carcinoma cells by downregulating the growth factor signaling. Issue 5 (20th August 2012) - Liu, Hu; Fu, Xiaohui; Ji, Weidan; Liu, Kai; Bao, Longlong; Yan, Yan; Wu, Mengchao; Yang, Jiahe; Su, Changqing
Abstract : Aim:  The human sulfatase‐1 ( hSulf‐1 ) gene regulates the sulfation of heparan sulfate proteoglycans (HSPG) and suppresses tumorigenesis and angiogenesis by inhibiting several growth factor signaling pathways. Because the serine‐threonine protein kinase (AKT) and extracellular signal‐regulated kinase (ERK) signaling pathways are critical in cell survival, proliferation, migration and angiogenesis, the possible correlation between hSulf‐1 and AKT/ERK signaling in hepatocellular carcinoma (HCC) cells needs further exploration. Methods:  Adenovirus Ad5‐hSulf1 carrying the hSulf‐1 gene, and vectors carrying hSulf‐1 shRNA, AKT shRNA and ERK shRNA were constructed and used to manipulate the expression of hSulf‐1, AKT and ERK in SMMC‐7721 cells. The scarification test, transwell and 3‐(4 5‐dimethylthiazol‐2‐yl)‐2 5‐diphenyltetrazolium bromide assays were used to examine the cellular migration and proliferation, and the expression of hSulf‐1 and signaling factors, including the total and phosphorylated AKT and ERK, was analyzed by western blot in SMMC‐7721 cells. Results:  After infection with Ad5‐hSulf1, the expression of hSulf‐1 was increased with viral multiplicity of infection in SMMC‐7721 cells. Compared with the control adenovirus Ad5‐EGFP and blank control groups, cells in the Ad5‐hSulf1 group were showed that the phosphorylation of AKT and ERK was decreased. Meanwhile, the cell migration and cell viability were obviously suppressed. Conclusion:  The expression of hSulf‐1 mediated by adenovirus in HCC cells could downregulate the activity of AKT and ERK signaling pathways, and inhibit HCC cell migration and proliferation. The hSulf‐1 gene may be considered as a candidate of antitumor factor for cancer gene therapy.